"Taqadmet" The Capital City Of Prince Abdelkader Of Algeria (Journal of Namibian Studies : History Politics Culture, 2024)
The biographies of the great men are few and far between, and those who have possessed all the virtues and qualities of perfection are rare, so they are found one after the other in the distant past, one after the other.He is the standard bearer of the jihad against the brutal French colonialists who invaded the land of Algeria, and we will look at a trace of the jihad of this man, especially his transformation from his capital, Camp, to the new capital, Taqadet, a capital that gained a great place with its glorious past and history, in the struggle of Prince Abdelkader for the liberation of Algeria.Through this study, we have tried to shed light on an important era in the biography of Amir Abdelkader, by highlighting the history of his new capital “Taqadet”, the reasons for his settlement there, and the prominent events in the life of Amir Abdelkader before he founded this city, and we will also look at the motives behind his settlement in this city and the reasons for his choice and its condition when he arrived there.Then we will return and talk about the most important buildings and facilities that were built during his reign and under his leadership, and finally we will conclude by talking about the French campaign against the city and the reason for its destruction and burning.